ENT 530 Social Media Portfolio: Groove / Afifitri Muhammad - Muhammad, Afifitri (2021)
Independent music is a very popular at my age. All the radio that times played independent song. “support local talent” was my moto in the groovy music store. The major objective in my company is to give them the real album of the band. In this globalization era, I know we have a lot of music’s streaming in the internet. But in Malaysia, we still have band that release album and they rely their income on it. So as fanatic of local talent, I make this company. My business began on the 16th of November 2020. My music store provides many local talent albums from 2000 until the latest. The latest band album its easy to find at many platforms such as carrousel, marketplace etc. But when you want to find the old Malaysian band album, it’s like the rare thing in here. Because of my passion in independent music, I choose to sell all the album inexpensive price. It is because I want to share my passion with others. The groovy music store has made a good started in this pandemic covid 19 . we get a lot of customer and they loved with our product and services. We hope we can gives the best services forever.